Pharmacological Inhibition of Lysine-Specific Demethylase 1A Reduces Atherosclerotic Lesion Formation in Apolipoprotein E-Deficient Mice by a Mechanism Involving Decreased Oxidative Stress and Inflammation; Potential Implications in Human Atherosclerosis - Simona-Adriana Manea; Mihaela-Loredana Vlad; Alexandra-Gela Lazar; Horia Muresian; Maya Simionescu; Adrian Manea (MDPI AG, 2022)
Dysregulated epigenetic mechanisms promote transcriptomic and phenotypic alterations in cardiovascular diseases. The role of histone methylation-related pathways in atherosclerosis is largely unknown. We hypothesize that lysine-specific demethylase 1A (LSD1/KDM1A) regulates key molecular effectors and pathways linked to atherosclerotic plaque formation. Human non-atherosclerotic and atherosclerotic tissue specimens, ApoE-/- mice, and in vitro polarized macrophages (Mac) were examined. Male ApoE-/- mice fed a normal/atherogenic diet were randomized to receive GSK2879552, a highly specific LSD1 inhibitor, or its vehicle, for 4 weeks. The mRNA and protein expression levels of LSD1/KDM1A were significantly elevated in atherosclerotic human carotid arteries, atherosclerotic aortas of ApoE-/- mice, and M1-Mac. Treatment of ApoE-/- mice with GSK2879552 significantly reduced the extent of atherosclerotic lesions and the aortic expression of NADPH oxidase subunits (Nox1/2/4, p22phox) and 4-hydroxynonenal-protein adducts. Concomitantly, the markers of immune cell infiltration and vascular inflammation were significantly decreased. LSD1 blockade down-regulated the expression of genes associated with Mac pro-inflammatory phenotype. Nox subunit transcript levels were significantly elevated in HEK293 reporter cells overexpressing LSD1. In experimental atherosclerosis, LSD1 mediates the up-regulation of molecular effectors connected to oxidative stress and inflammation. Together, these data indicate that LSD1-pharmacological interventions are novel targets for supportive therapeutic strategies in atherosclerosis.